International sign : linguistic, usage, and status issues (Sociolinguistics in deaf communities series, 2015)
International Sign (IS) is widely used among deaf people and interpreters at international events, but what exactly is it, what are its linguistic features, where does its lexicon come from, and how is it used at interpreted events? This groundbreaking collection is the first volume to provide answers to these questions. Editors Rachel Rosenstock and Jemina Napier have assembled an international group of renowned linguists and interpreters to examine various aspects of International Sign. Their contributions are divided into three parts: International Sign as a Linguistic System; International Sign in Action--Interpreting, Translation, and Teaching; and International Sign Policy and Language Planning. The chapters cover a range of topics, including the morphosyntactic and discursive structures of interpreted IS, the interplay between conventional linguistic elements and nonconventional gestural elements in IS discourse, how deaf signers who use different signed languages establish communication, Deaf/hearing IS interpreting teams and how they sign depicting verbs, how best to teach foundation-level IS skills, strategies used by IS interpreters when interpreting from IS into English, and explorations of the best ways to prepare interpreters for international events. The work of the editors and contributors in this volume makes International Sign the most comprehensive, research-based analysis of a young but growing field in linguistics and interpretation.